2017
DOI: 10.1016/j.ejwf.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cone-beam computed tomography evaluation of bone density of midpalatal suture before, after, and during retention of rapid maxillary expansion in growing patients

Abstract: Objective: To analyze changes in bone density of the midpalatal suture after rapid palatal expansion (RME) with the Hyrax-type expander in growing subjects using cone-beam computed tomography (CBCT). Materials: Fourteen patients (nine girls and five boys; mean age, 11.7 AE 2.4 years) who required RME as part of their orthodontic treatment and had preexpansion (T0) and postexpansion (at the end of active expansion [T1], after a retention period of 3 months [T2], and after 6-month [T3] retention period) CBCT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…A few studies 12,22 have actually found a linear relationship between CBCT and MDCT measurements by multiplying the CBCT value by 0.7 to get the MDCT value. While absolute BD values cannot be accurately determined using CBCT, trends can be identified by using relative BD values 13,23 . Due to this discrepancy, the measurement of mandibular symphysis BD values is used as relative values and not absolute values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies 12,22 have actually found a linear relationship between CBCT and MDCT measurements by multiplying the CBCT value by 0.7 to get the MDCT value. While absolute BD values cannot be accurately determined using CBCT, trends can be identified by using relative BD values 13,23 . Due to this discrepancy, the measurement of mandibular symphysis BD values is used as relative values and not absolute values.…”
Section: Discussionmentioning
confidence: 99%
“…When Kim et al 11 investigated the condylar head BD, they found higher BD in the condylar head for TA B L E 1 Mandibular symphysis bone density according to gender and skeletal pattern (HU) The symphysis BD was higher in females than males which were consistent with some previous studies 11,15 absolute BD values cannot be accurately determined using CBCT, trends can be identified by using relative BD values. 13,23 Due to this discrepancy, the measurement of mandibular symphysis BD values is used as relative values and not absolute values. CBCT is becoming increasingly more popular in orthodontics because the amount of radiation exposure to patients can be less than with a traditional panorex and cephalogram under certain conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive data of the ten included studies are summarized in Table 3, in wh it is possible to observe that half of the studies were retrospective [23][24][25][26][27] and the ot…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The descriptive data of the ten included studies are summarized in Table 3, in which it is possible to observe that half of the studies were retrospective [23][24][25][26][27] and the other half were prospective [13,15,16,28,29]. A total of 215 patients were included: 158 females and 57 males.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%